Proses digitisasi karya ilmiah lama di Perpustakaan Fakultas Pertanian Universitas Padjadjaran - Anjani, Salsabiila; Rizal, Edwin; Saepudin, Encang (Faculty of Communication, Padjadjaran University, 2024)
Because the Padjadjaran University Faculty of Agriculture Library has so many scholarly books, there is a mountain of accumulation inside of it. Science work is damp, moldy, and dirty. Furthermore, it is very challenging to find scientific articles later due to the mountains of them. The University of Padjadjaran Library's digitalization initiatives are predicated on this understanding. Examining the process of digitizing historical scientific articles (published prior to 2016) in the University of Padjadjaran's Faculty of Agriculture Library is the aim of this study. The research methodology used is a case study methodology using a qualitative approach. In order to gather data, observations and interviews are conducted. Interviews were conducted with the coordinator of digitization activities at the Library of the Faculty of Agriculture, University of Padjadjaran, digitization staff, and students who had done digitalization internships. Data analysis uses data reduction techniques, data presentation, and verification. The study's findings indicated that this digitizing process had previously been done, halted, and then continued till the present. The first step involves scanning; the second involves editing the results of the scanning process, such as adding a watermark or a password, but this step has not yet been completed; the three uploading procedures are uploaded to the Unpad Faculty of Agriculture Library's Google Drive. The last phase involves scanning and destroying the physical scientific works; nevertheless, official protocols have not been followed in this process. The study's findings demonstrate that while the digitization efforts undertaken are generally excellent, crucial information pertaining to particular SOPs at every stage of the process is still lacking.